Stress of Elderly People and its Consequences for Mental Health - Valiulienė, Žaneta; Stalnionienė, Loreta; Petravičienė, Zita; Bartašiūnienė, Vida (Slauga. Mokslas ir praktika, 2023)
If not managed properly, stress can interfere with the ability of elderly people to maintain their well-being.Mental health is an important part of health care that needs to be talked about not only in mental health settings but also in society.Typically, people prepare for retirement only in the financial sphere and not in other social aspects. Many older people feel unappreciated and lonely. Such situations are usually stressful for older people. As for stress in general, if an elderly person is unable to cope with it, it can lead to the physical decline of the elderly person. Older people are stressed by changes in their lifestyle. A lot of routine with excellent physical conditions is a dream for elderly people. Some elderly people without financial stability still must perform routine activities without good physical conditions [11,12].The study was based on scientific articles and other scientific literature found in the medical databases UpToDate and PubMed. The search was carried out using the following keywords and combinations: stress, mental health, elderly person. The aim was to review the scientific literature on the stress experienced by elderly people and its consequences for mental health.Conclusions. A review of the scientific literature suggests that with the rapid increase in the number of elderly people in the world, it is important to maintain a good physical and emotional state of health. Poorly managed stress can have a negative impact not only on a person's daily activities, but also on physical health and emotional well-being.Constant stress reduces quality of life and communication with the outside world. Anxiety leads to excessive feelings of fear or frustration, which ultimately have a negative impact on a person's health. Participation in leisure activities has been shown to significantly improve social support and mental health for elderly people.
Keywords: stress; mental health; elderly person